2012
DOI: 10.1007/s00277-012-1636-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic elevated asymmetric dimethylarginine (ADMA) levels on granulopoiesis

Abstract: The endogenous nitric oxide synthase inhibitor asymmetric dimethylarginine (ADMA) is elevated in both animal models of chronic inflammatory disorders as well as in patients with chronic inflammatory disease. In vivo data suggest that ADMA can increase the number of circulating monocytes and possibly affect their adhesion potential in vitro. The aim of our study was to evaluate possible effects of chronically elevated levels of ADMA on white blood cell count (WBC), leukocyte subsets, and WBC distribution patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Given that monocytes express eNOS and that DOX causes elevated ADMA formation, we speculate that DOX could influence monocytic-eNOS to undergo uncoupling via ADMA accumulation, leading to endothelial dysfunction. ii) An in vivo study reports that circulating ADMA increases the number of circulating monocytes which in turn affects their adhesion potential, thereby accelerating monocyte-endothelial cell adhesion [50] . This adhesion down regulates the steady state levels of eNOS along with attenuated release of nitric oxide, thus contributing to endothelial dysfunction [51] .…”
Section: Discussionmentioning
confidence: 99%
“…Given that monocytes express eNOS and that DOX causes elevated ADMA formation, we speculate that DOX could influence monocytic-eNOS to undergo uncoupling via ADMA accumulation, leading to endothelial dysfunction. ii) An in vivo study reports that circulating ADMA increases the number of circulating monocytes which in turn affects their adhesion potential, thereby accelerating monocyte-endothelial cell adhesion [50] . This adhesion down regulates the steady state levels of eNOS along with attenuated release of nitric oxide, thus contributing to endothelial dysfunction [51] .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our finding, they also concluded that circulating ADMA concentrations are not altered by venous thromboembolism [ 29 ]. In a recent animal study, it might be worthwhile to mention that even long term infusion of ADMA (in a preclinical model) did at least not affect peripheral numbers of erythrocytes, leukocytes, and thrombocytes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%